Functional Analysis of the Oil Palm Metallothioninelike Gene Promoter Using Transient Expression Assay - Izadfard, Amir (2009)
The metallothionein-like gene, MT3-A, is specifically and abundantly expressed in the mesocarp tissue of the oil palm, Elaeis guineensis. In order to characterize the MT3-A promoter, a functional analysis containing bioinformatics and deletion analysis were carried out. The MT3-A promoter was subjected to bioinformatics analysis using three online data bases including PLACE, TESS and Softberry and with the assistance of the DNASIS software to identify and determine the position of the various regulatory motifs. Bioinformatics survey of the MT3-A promoter showed the presence of more than 50 reported regulatory motifs and the motifs of interest includes an I-box from Monocots/ Dicots at position -944, G-box from Phaseolus vulgaris at position -745 and ERE reverse from Lycopersicon esculentum at position -317. To gain further insight into the mechanism that regulates the transcriptional activity of the metallothionein-like gene, analysis of the 5'-deletion series of the 986 bp oil palm MT3-A promoter using transient expression assay was carried out. Six promoter fragments of 823, 620, 470, 332, 181, 115 bp were generated by PCR and cloned into promoter-less pEGFP-1 carrying green fluorescent protein (GFP) by introducing Hind III and Pst I sites. The vector construct containing the different MT3-A promoter fragment was co-bombarded with a vector construct carrying CaMV promoter linked to GUS (pBI221) reporter gene into oil palm mesocarp and leaf tissues. Each deletion construct was bombarded to samples from each tissue type. The ratio of GFP/GUS or green/blue fuci was determined in each construct bombarded and taken as the percentage of the construct giving the highest expression. Based on the transient assay analysis, it was found that the 620 bp and 823 bp truncated versions of the MT3-A promoter gave higher expression in the mesocarp compared with the whole 986 bp promoter. But the 470 bp and 332 bp fragments showed decreasing level of expression compared to the full length. These results suggest that at least there are two negative regulatory elements upstream of the positions -823 as well as between -620 and -823. It was noted that production of the 823 bp promoter fragment involves removing the I-box which has been reported to act as a negative regulatory element in a fruit-specific promoter. The decrease in expression level suggests that there is a positive regulatory element upstream of the -470 region as well as between -332 and -470 of the MT3-A promoter. The expression in the leaves was only detectable in the four smallest fragments upon the removal of mesocarp-specific regulatory element upstream of the position -470. Alignment of the MT3-A promoter with the promoter of a closely related MT3-B gene which is expressed in both mesocarp and root suggested that there is a ten base-pair motif (AATTTCCTtC) in both of these promoters in the MT3-A promoter region (between -332 and -470) which has lost its mesocarp specificity. This motif is located at about the same position [-360 (MT3-A) and -346 (MT3-B) ] from the transcription start site in both promoters. To have an insight on the role of this novel motif, an eight tandem repeat of this motif were synthesized. The constructs carrying this tandem repeats of the motifs in the forward and reverse orientation fused to minimal MT3-A promoter in pEGFP-1 were produced and used to bombard mesocarp and leaf tissues of the oil palm. The results suggest that this tandem repeat motif in both forward and reverse orientation could increase the expression of GFP reporter gene in the mesocarp. It was observed that both the forward and reverse orientation of the motif could decrease the level of GFP reporter gene expression in leaf tissue slices.